A covalent organic framework material rich in thiophene rings and a preparation method and application thereof

CN122325693BActive Publication Date: 2026-09-08HUNAN INSTITUTE OF ENGINEERING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610719231.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-25
Publication Date
2026-09-08
Estimated Expiration
2046-05-25

AI Technical Summary

Technical Problem

[0010]针对现有共价有机框架材料在光催化制备过氧化氢中存在的合成复杂、稳定性差、催化活性低、选择性不足等技术问题,本发明提供一种富含噻吩环的共价有机框架材料及其制备方法与应用

Benefits of technology

[0029] (1) Mild preparation process: The solvothermal reaction is adopted, which does not require high temperature and high pressure. The post-processing is simple, the whole process is green and pollution-free, the energy consumption is low, the cost is low, and it is easy to scale up production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122325693B_ABST
    Figure CN122325693B_ABST
Patent Text Reader

Abstract

The application discloses a kind of covalent organic framework materials rich in thiophene ring and its preparation method and application, belong to semiconductor photocatalytic material technical field.1,3,5-Three [2-cyano-2-(4-aminophenyl) vinyl] benzene is amine monomer, 2,5-di (thiophene-2-yl) p-benzenedialdehyde is aldehyde monomer, and the LTP-COF material rich in thiophene ring is prepared by solvothermal reaction.The material forms large size conjugated system and rich thiophene ring active site inside, visible light absorption ability is strong, photoinduced carrier separation and transport efficiency are high, and the photocatalytic production rate of hydrogen peroxide in water can be as high as 4805 μmolg ‑ 1 h ‑1 The application process condition is mild, green and environment-friendly, low in cost, easy to scale production, and the obtained material is excellent in catalytic activity, selectivity and stability, significantly better than existing covalent organic framework photocatalyst, and has important application value in the field of photocatalytic green preparation of hydrogen peroxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor photocatalytic materials technology, specifically relating to a covalent organic framework material rich in thiophene rings, its preparation method, and its application. Background Technology

[0002] Hydrogen peroxide (H2O2), as a highly efficient and environmentally friendly oxidant, is widely used in many fields such as chemical synthesis, environmental pollutant degradation, medical and health disinfection, and paper bleaching, making it an indispensable chemical in modern industry and people's lives. Currently, large-scale industrial production of H2O2 mainly employs the anthraquinone process. This method requires high temperature and high pressure conditions, resulting in high energy consumption, complex processes, numerous byproducts, and potential organic pollution. Furthermore, the reaction conditions are stringent, requiring sophisticated equipment, which is inconsistent with the trend of green and low-carbon development. Therefore, developing mild, efficient, green, and low-cost H2O2 preparation technologies has become a research hotspot in the field of catalysis.

[0003] Photocatalytic synthesis of H2O2, driven by solar energy and using water and oxygen as raw materials, can achieve green synthesis of H2O2 at room temperature and pressure. It boasts advantages such as mild reaction conditions, environmental friendliness, and low energy consumption, and is considered one of the most promising routes for H2O2 preparation. Covalent organic frameworks (COFs) are a class of crystalline porous materials formed by organic monomers linked by covalent bonds. They possess advantages such as large specific surface area, ordered pore structure, strong structural designability, and tunable light absorption performance, showing great application potential in photocatalytic reactions.

[0004] In recent years, researchers have developed a variety of COF materials for photocatalytic H2O2 production, but existing technologies still have many shortcomings:

[0005] (1) Existing COF materials synthesis requires high temperature, high pressure and long reaction time, which is complicated, cumbersome post-processing, and high preparation cost, making it difficult to achieve large-scale production;

[0006] (2) Most COF materials have poor structural stability and are prone to collapse in aqueous solutions, resulting in poor photocatalytic recycling performance;

[0007] (3) The material has a narrow visible light absorption range, a high recombination rate of photogenerated carriers, a low catalytic reaction rate, and an H2O2 generation efficiency that is difficult to meet the needs of practical applications.

[0008] (4) Catalytic selectivity is difficult to control, byproducts are easily generated, and product purity is low.

[0009] Therefore, there is an urgent need to develop a COF material with simple preparation process, mild conditions, stable structure, strong visible light response, high carrier separation efficiency, and excellent catalytic activity to solve the bottleneck problem of existing technology in the field of photocatalytic preparation of H2O2. Summary of the Invention

[0010] To address the technical problems of existing covalent organic framework materials in the photocatalytic preparation of hydrogen peroxide, such as complex synthesis, poor stability, low catalytic activity, and insufficient selectivity, this invention provides a covalent organic framework material rich in thiophene rings, its preparation method, and its application.

[0011] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0012] The thiophene ring-rich covalent organic framework material provided by this invention is formed by the condensation of the amine monomer 1,3,5-tris[2-cyano-2-(4-aminophenyl)vinyl]benzene (BTAC) and the aldehyde monomer 2,5-bis(thiophene-2-yl)terephthalaldehyde (DTT) via imine bonds. It is internally rich in thiophene ring active sites and a cyano-functionalized conjugated system, denoted as LTP-COF, and its structural formula is as follows:

[0013] ;

[0014] LTP-COF exhibits a photocatalytic hydrogen peroxide production rate of 3000-5000 μmolg under visible light. -1 h -1 .

[0015] Furthermore, the X-ray diffraction pattern of LTP-COF material exhibits characteristic sharp diffraction peaks in the range of 2°-10°, and its microstructure is spherical, demonstrating good crystallinity and porous structure.

[0016] The preparation method of the above-mentioned covalent organic framework material rich in thiophene rings includes the following steps:

[0017] S1. Synthesis of the amine monomer BTAC: Trimethylbenzenealdehyde, p-aminophenylacetonitrile, and a base are reacted in a mixed solvent under a protective atmosphere at 75-95℃ for 2-4 hours. After washing and drying, the amine monomer 1,3,5-tris[2-cyano-2-(4-aminophenyl)vinyl]benzene, abbreviated as BTAC, is obtained. Its chemical reaction formula is as follows:

[0018] ;

[0019] S2. Synthesis of aldehyde monomer DTT: 2,5-Dibromophenyl-1,4-dicarboxaldehyde, pinacol thiophene-2-borate, a base, and a catalyst are added to a mixed solvent. The reaction is carried out at 90-110℃ for 20-28 hours under a protective atmosphere. After washing and drying, the aldehyde monomer 2,5-bis(thiophene-2-yl)-terephthalaldehyde, abbreviated as DTT, is obtained. Its chemical reaction formula is as follows:

[0020] ;

[0021] Synthesis of S3 and LTP-COF: BTAC and DTT were dissolved in an organic solvent, an acidic catalyst was added, and after sonication, degassing, and vacuum sealing, the mixture was reacted at a constant temperature of 110-130℃ for 2-4 days. LTP-COF was obtained after separation, washing, and drying.

[0022] Further, in step S1, the mixed solvent is a mixture of ethanol and water, with a volume ratio of ethanol to water of 1:(0.8-1.2), the base is sodium hydroxide, and the molar ratio of pyromellitic aldehyde to p-aminophenylacetonitrile is 1:(3.2-3.6).

[0023] Further, in step S2, the mixed solvent is a mixture of 1,4-dioxane and water, with a volume ratio of 1,4-dioxane to water of (9-11): the molar ratio of 1,2,5-dibromophenyl-1,4-dicarboxaldehyde to thiophene-2-boronic acid pinacol ester of 1:(2.2-3.0), and the catalyst is tetrakis(triphenylphosphine)palladium. This step employs a Suzuki coupling reaction to directionally construct a bisthiophene ring functionalized aldehyde monomer. The introduction of the thiophene ring provides abundant catalytic active sites and broadens the visible light absorption range. Suitable raw material ratios, mild reaction temperatures, and reaction times ensure high monomer purity and high yield, while avoiding damage to the thiophene ring structure.

[0024] Further, in step S3, the organic solvent is a mixture of n-butanol and o-dichlorobenzene, with a volume ratio of 1:(0.8-1.2), the acidic catalyst is acetic acid, and the molar ratio of BTAC to DTT is 1:(0.9-1.1).

[0025] Furthermore, an acetic acid solution with a concentration of 4-8 mol / L is used to ensure that the condensation reaction proceeds rapidly while avoiding excessive acidity that could lead to framework hydrolysis or structural collapse, thus giving the resulting LTP-COF both high crystallinity and high structural stability.

[0026] Furthermore, in step S3, the ultrasonic time is 10-20 minutes, the degassing is carried out by liquid nitrogen bath freezing-pumping-thawing cycle 2-4 times, and the drying is vacuum drying for 20-28 hours.

[0027] The aforementioned covalent organic framework material rich in thiophene rings is used for the photocatalytic preparation of hydrogen peroxide. The photocatalytic reaction uses water as the reaction medium, with LTP-COF material as the photocatalyst, and is carried out under visible light irradiation. The cyano conjugated system in LTP-COF and the active site of the thiophene ring work synergistically to significantly enhance visible light absorption and accelerate carrier separation and transport, resulting in a hydrogen peroxide yield that is significantly better than that of existing COF materials. At the same time, the material is structurally stable in aqueous solution, does not easily swell or collapse, has excellent recyclability, and has the potential for large-scale application.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0029] (1) Mild preparation process: The solvothermal reaction is adopted, which does not require high temperature and high pressure. The post-processing is simple, the whole process is green and pollution-free, the energy consumption is low, the cost is low, and it is easy to scale up production.

[0030] (2) The material obtained by this invention is rich in thiophene ring active sites and cyano group conjugated system, has strong visible light absorption, high photogenerated carrier separation efficiency, and H2O2 generation rate as high as 4805 μmolg. -1 h -1 It is superior to most existing COF photocatalysts.

[0031] (3) The material obtained by the present invention has a stable structure, excellent catalytic selectivity and recycling performance, and can be widely used in the green preparation of H2O2 in the fields of chemical industry, environmental governance, medical and health care. Attached Figure Description

[0032] Figure 1 , Figure 2 The X-ray diffraction patterns are for LTP-COF and CPT-COF, respectively.

[0033] Figure 3 , Figure 4 Transmission electron micrographs of LTP-COF and CPT-COF, respectively.

[0034] Figure 5 The Fourier transform infrared spectra of LTP-COF and CPT-COF are shown.

[0035] Figure 6 The graph shows the rate curves of photocatalytic hydrogen peroxide production by LTP-COF and CPT-COF under conditions of no sacrificial agent, visible light irradiation, and oxygen saturation.

[0036] Figure 7 The transient photocurrent response diagrams for LTP-COF and CPT-COF are shown. Detailed Implementation

[0037] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0038] Example 1

[0039] Step 1: Synthesis of the amine monomer BTAC

[0040] 300 mg (1.852 mmol) of trimesin, 855 mg (6.482 mmol) of p-aminophenylacetonitrile, and 600 mg (15 mmol) of sodium hydroxide were dissolved in a mixed solvent of 10 mL ethanol and 10 mL water. The reaction mixture was refluxed at 85 °C for 3 hours under an argon atmosphere. After the reaction, the product was washed sequentially with sodium hydroxide solution, water, and ethanol, with each washing operation repeated three times. The product was then dried overnight to obtain a yellow solid, BTAC.

[0041] Step 2: Synthesis of the aldehyde monomer DTT

[0042] A reaction system was prepared by mixing 146 mg (0.5 mmol) of 2,5-dibromophenyl-1,4-dicarboxaldehyde, 262.6 mg (1.25 mmol) of pinacol thiophene-2-borate, 414.6 mg (3 mmol) of potassium carbonate, 20 mL of 1,4-dioxane, and 2 mL of water. The mixture was bubbled for 30 minutes. After bubbling, 40.0 mg of tetra(triphenylphosphine)palladium was added. Under a nitrogen atmosphere, the mixture was heated to 100 °C and stirred continuously for 24 hours. After the reaction was complete, the reactants were cooled to room temperature and then poured into 100.0 mL of water. The residual product was washed repeatedly with excess water, methanol, toluene, and chloroform. After washing, the product was dried at 60 °C to obtain DTT.

[0043] Step 3: Synthesis of LTP-COF

[0044] BTAC 25.2 mg (0.05 mmol), DTT 20.4 mg (0.05 mmol), n-butanol 1.8 mL, o-dichlorobenzene 1.8 mL, and 6 mol / L acetic acid aqueous solution 0.2 mL were added sequentially to a Pyrex reaction tube. The reaction tube was then sonicated for 15 minutes, followed by three freeze-pump-thaw cycles in a liquid nitrogen bath at 77 K. After these steps, the reaction tube was sealed under vacuum and placed in an oven at 120 °C for 3 days. A yellow precipitate formed during the reaction. The precipitate was separated by centrifugation and washed sequentially with tetrahydrofuran and acetone. After washing, the sample was dried in a vacuum drying oven for 24 hours to obtain the yellow powder product LTP-COF with a yield of 86.3%. The chemical reaction formula is as follows:

[0045] .

[0046] The LTP-COF photocatalytic H2O2 production rate obtained in Example 1 was tested to be 4805 μmol / g.-1 h -1 .

[0047] Example 2

[0048] Step 1: Synthesis of the amine monomer BTAC

[0049] 300 mg of trimesin, 820 mg of p-aminophenylacetonitrile, and 600 mg of sodium hydroxide were dissolved in a mixed solvent of 9.5 mL of ethanol and 10 mL of water, and refluxed at 80 °C for 2.5 hours under argon protection. The post-treatment was the same as in Example 1 to obtain BTAC.

[0050] Step 2: Synthesis of the aldehyde monomer DTT

[0051] 146 mg of 2,5-dibromobenzene-1,4-dicarboxaldehyde, 252 mg of thiophene-2-borate pinacol ester, 414.6 mg of potassium carbonate, 19 mL of 1,4-dioxane, and 2 mL of water were mixed and bubbled for 30 minutes. 40.0 mg of tetrakis(triphenylphosphine)palladium was then added. The reaction was carried out at 95°C for 22 hours under nitrogen protection. The post-treatment was the same as in Example 1, yielding DTT.

[0052] Step 3: Synthesis of LTP-COF

[0053] Add 25.2 mg BTAC, 20.4 mg DTT, 1.7 mL n-butanol, 1.8 mL o-dichlorobenzene, and 0.2 mL 5 mol / L acetic acid aqueous solution to a Pyrex reaction tube. Sonicate for 12 minutes, cycle twice in a liquid nitrogen bath at 77 K, and then seal under vacuum. React at 115 °C for 2.5 days. Centrifuge, wash, and vacuum dry for 24 hours to obtain LTP-COF, with a yield of 84.7%.

[0054] The LTP-COF photocatalytic H2O2 production rate obtained in Example 2 was tested to be 4218 μmol / g. -1 h -1 .

[0055] Example 3

[0056] Step 1: Synthesis of the amine monomer BTAC

[0057] 300 mg of trimesin, 890 mg of p-aminophenylacetonitrile, and 600 mg of sodium hydroxide were dissolved in a mixed solvent of 10.5 mL ethanol and 10 mL water, and refluxed at 90 °C for 3.5 hours under argon protection. The post-treatment was the same as in Example 1 to obtain BTAC.

[0058] Step 2: Synthesis of the aldehyde monomer DTT

[0059] 146 mg of 2,5-dibromobenzene-1,4-dicarboxaldehyde, 273 mg of thiophene-2-borate pinacol ester, 414.6 mg of potassium carbonate, 21 mL of 1,4-dioxane, and 2 mL of water were mixed and bubbled for 30 minutes. Then, 40.0 mg of tetra(triphenylphosphine)palladium was added, and the mixture was reacted at 105°C for 26 hours under nitrogen protection. The post-treatment was the same as in Example 1 to obtain DTT.

[0060] Step 3: Synthesis of LTP-COF

[0061] 25.2 mg BTAC, 20.4 mg DTT, 1.9 mL n-butanol, 1.8 mL o-dichlorobenzene, and 0.2 mL 7 mol / L acetic acid aqueous solution were added to a Pyrex reaction tube. The mixture was sonicated for 18 minutes, circulated four times in a liquid nitrogen bath at 77 K, and then sealed under vacuum and reacted at 125 °C for 3.5 days. After centrifugation, washing, and vacuum drying for 24 hours, LTP-COF was obtained with a yield of 84.7%.

[0062] The LTP-COF photocatalytic H2O2 production rate obtained in Example 3 was tested to be 4690 μmol / g. -1 h -1 .

[0063] Comparative Example 1

[0064] The rest is the same as in Example 1, except that the aldehyde monomer DTT in step three is replaced with an equal amount of the conventional monomer 5,5',5''-(benzene-1,3,5-triyl)tris(thiophene-2-carboxaldehyde) (Tri-FT). The product is a dark yellow powder, denoted as CPT-COF, with a yield of 80.5%. Its chemical reaction formula is as follows:

[0065] .

[0066] The CPT-COF photocatalytic H2O2 production rate obtained in Comparative Example 1 was tested to be 2960 μmol / g. -1 h -1 .

[0067] Comparative Example 2

[0068] The rest is the same as in Example 1, except that the 2,5-dibromobenzene-1,4-dicarboxaldehyde in step two is replaced with an equimolar amount of benzoxaldehyde monomer.

[0069] The photocatalytic H2O2 production rate of the material obtained in Comparative Example 2 was tested to be 1820 μmol / g. -1 h -1 .

[0070] Comparative Example 3

[0071] The rest is the same as in Example 1, except that the reaction temperature in step three is increased from 120°C to 150°C.

[0072] The photocatalytic H2O2 production rate of the material obtained in Comparative Example 3 was tested to be 1245 μmol / g. -1 h -1 The reason is that the reaction temperature was too high, which damaged the material structure.

[0073] LTP-COF is illustrated using the product obtained in Example 1 as a typical example.

[0074] The X-ray diffraction patterns of LTP-COF and CPT-COF are as follows: Figure 1 and Figure 2 As shown. By Figure 1 and Figure 2 It can be seen that both materials exhibit characteristic sharp diffraction peaks in the range of 2°-10°, and the presence of these characteristic peaks indicates that both LTP-COF and CPT-COF have been successfully prepared.

[0075] Transmission electron micrographs of LTP-COF and LTP-COF are shown below. Figure 3 and Figure 4 As shown, the material exhibits a spherical microstructure.

[0076] The Fourier transform infrared spectra of LTP-COF and CPT-COF are as follows: Figure 5 As shown. By Figure 5 It can be concluded that the two materials at 1700cm -1 The characteristic absorption peaks of the aldehyde group at the corresponding position have all disappeared, and at ~1627 cm⁻¹, the characteristic absorption peaks of the aldehyde group have all disappeared. -1 The presence of a characteristic absorption peak for an imine bond indicates the successful formation of the imine bond.

[0077] Figure 6 The graphs show the photocatalytic hydrogen peroxide production rates of LTP-COF and CPT-COF under visible light irradiation. The photocatalytic H₂O₂ production rate of LTP-COF can reach 4805 μmol / g. -1 h -1 It is significantly superior to CPT-COF (2960 μmolg). -1 h -1 The results show that the prepared material is significantly better than most covalent organic framework photocatalysts reported to date, indicating that the prepared material has excellent photocatalytic activity.

[0078] The photocurrent response test results of LTP-COF and CPT-COF are shown below. Figure 7 As shown. By Figure 7 It can be seen that LTP-COF has a high photocurrent response value, which indirectly proves that it has excellent light absorption and photogenerated carrier separation capabilities.

Claims

1. An application of a covalent organic framework material rich in thiophene rings, characterized in that, The covalent organic framework material is used as a catalyst for the photocatalytic preparation of hydrogen peroxide. The photocatalytic reaction is carried out under visible light irradiation with water as the reaction medium. The covalent organic framework material is formed by the condensation of the amine monomer 1,3,5-tris[2-cyano-2-(4-aminophenyl)vinyl]benzene and the aldehyde monomer 2,5-di(thiophene-2-yl)-terephthalaldehyde via imine bond condensation. It is rich in thiophene ring active sites and cyano functionalized conjugated systems, denoted as LTP-COF, and its structural formula is as follows: ; The X-ray diffraction pattern of the covalent organic framework material has characteristic sharp diffraction peaks in the range of 2°-10°, and its microstructure is spherical. The preparation method of the covalent organic framework material rich in thiophene rings includes the following steps: S1. Synthesis of amine monomer BTAC: Trimethylbenzene, p-aminophenylacetonitrile and base are reacted with a base in a mixed solvent and refluxed at 75-95℃ for 2-4 hours under a protective atmosphere. After washing and drying, the amine monomer 1,3,5-tris[2-cyano-2-(4-aminophenyl)vinyl]benzene is obtained, abbreviated as BTAC. S2. Synthesis of aldehyde monomer DTT: 2,5-dibromophenyl-1,4-dicarboxaldehyde, thiophene-2-boronic acid pinacol ester, base and catalyst are added to a mixed solvent. The reaction is carried out at 90-110℃ for 20-28 hours under a protective atmosphere. After washing and drying, the aldehyde monomer 2,5-bis(thiophene-2-yl)terephthalaldehyde, abbreviated as DTT, is obtained. Synthesis of S3 and LTP-COF: BTAC and DTT were dissolved in an organic solvent, an acidic catalyst was added, and after sonication, degassing, and vacuum sealing, the mixture was reacted at a constant temperature of 110-130℃ for 2-4 days. LTP-COF was obtained after separation, washing, and drying.

2. The application as described in claim 1, characterized in that, In step S1, the mixed solvent is a mixture of ethanol and water, with a volume ratio of ethanol to water of 1:(0.8-1.2), the alkali is sodium hydroxide, and the molar ratio of pyromellitic acetonitrile to p-aminophenylacetonitrile is 1:(3.2-3.6).

3. The application as described in claim 1, characterized in that, In step S2, the mixed solvent is a mixture of 1,4-dioxane and water, the volume ratio of 1,4-dioxane to water is (9-11): the molar ratio of 1,2,5-dibromobenzene-1,4-dicarboxaldehyde to thiophene-2-boronic acid pinacol ester is 1:(2.2-3.0), and the catalyst is tetrakis(triphenylphosphine)palladium.

4. The application as described in claim 1, characterized in that, In step S3, the organic solvent is a mixture of n-butanol and o-dichlorobenzene, with a volume ratio of 1:(0.8-1.2), and the acidic catalyst is acetic acid, with a molar ratio of BTAC to DTT of 1:(0.9-1.1).

5. The application as described in claim 4, characterized in that, The acetic acid used is an acetic acid solution with a concentration of 4-8 mol / L.

6. The application as described in claim 1, characterized in that, In step S3, the ultrasonic time is 10-20 minutes, the degassing is carried out by liquid nitrogen bath freezing-pumping-thawing cycle 2-4 times, and the drying is vacuum drying for 20-28 hours.